A Child With Autism Spectrum Disorder Teaches Siblings to Skateboard: Effects on Sibling Skills and Family Social Behavior. Issue 3 (3rd July 2019) - Thomas, Benjamin R.; Lafasakis, Michael; Spector, Vicki
Abstract: Children with autism spectrum disorder (ASD) may have few common activities with their siblings who do not have ASD, and this can limit their opportunities for social play. In this study, we used a multiple-baseline across skills design to assess the effects of a boy with ASD following an activity schedule to teach his favorite activity of skateboarding to his two siblings who do not have ASD. Family social behavior was also measured before and after sibling training. After training by the boy with ASD, both of the siblings' skateboarding skills improved, and measures of family social behavior also increased. Results suggest that sibling relationships may benefit when a child with ASD teaches siblings to play.